Impurities: an aesthetic reflection - Moreira, Tânia (CEM – Cultura, Espaço & Memória, 2019)
The history of aesthetic ideas has explored, from its beginnings, an incompatibility between aesthetics and perfection. On the one hand, this explains the tension found in Plato and Aristotle between the prescribed theory and the practice. On the other hand, it also explains the modern claim of imperfection — as an attribute of the work of art — in authors such as Victor Hugo and Baudelaire. In fact, this claim was only possible in the wake of the third Kantian Critique, which restored the foundations of aesthetics while removing the idea of perfection as end. This essay proposes that an aesthetics of imperfection rests not on an apology of chance and error, but that flaw rises in the exercise of maximum freedom linked to a maximal demand. Whether in creation or reception, aesthetic experience implies moving on a risky course, without guarantees or safety.